2022
DOI: 10.3390/horticulturae8090830
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Spent Mushroom Substrate Biochar and PGPR Improves Growth, Yield, and Biochemical Response of Cauliflower (Brassica oleracea var. botrytis): A Preliminary Study on Greenhouse Cultivation

Abstract: This paper investigated the impact of the combined use of spent mushroom substrate (SMS) biochar and plant-growth-promoting rhizobia (PGPR) on the growth, yield, and biochemical response of cauliflower (Brassica oleracea var. botrytis). A preliminary study was conducted under greenhouse condition using six treatments (sextuplicate) as control (no addition), T1 (PGPR), T2 (5 g/Kg biochar), T3 (5 g/Kg biochar + PGPR), T4 (10 g/Kg biochar), and T5 (10 g/Kg biochar + PGPR) under greenhouse conditions. The Scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Similarly, Zawadzi ńska et al [43] attributed the higher fresh tomato weights of compost growing media to the greater availability and uptake of nutrients. Although the influence of biochar on growing substrate properties and plant growth has been widely studied [17,19,49], little is known about the effects on horticultural fruit production. In this regard, Massa et al [50] reported that BC stimulated tomato plant growth but not fruit yield, suggesting that replacing peat with biochar-based growing media represents a valuable strategy for improving plant biomass instead of crop yield.…”
Section: Fruit Productionmentioning
confidence: 99%
“…Similarly, Zawadzi ńska et al [43] attributed the higher fresh tomato weights of compost growing media to the greater availability and uptake of nutrients. Although the influence of biochar on growing substrate properties and plant growth has been widely studied [17,19,49], little is known about the effects on horticultural fruit production. In this regard, Massa et al [50] reported that BC stimulated tomato plant growth but not fruit yield, suggesting that replacing peat with biochar-based growing media represents a valuable strategy for improving plant biomass instead of crop yield.…”
Section: Fruit Productionmentioning
confidence: 99%
“…Names of the active compounds and their percentages in coriander oil grown in the treatment of mushroom residues without the addition of mycorrhizae. The results of the GC-mass chromatography analysis in Table (10) showed the presence of 167 chemical compounds of the aromatic oil produced from the cultivation of coriander plants in the soil of the fungus residues with the addition of mycorrhizae, and the proportions of the compounds ranged between 0.01 and 23.25%, as only 23 compounds were taken into the table because their percentage was more than 1%. The first 5 compounds in the table are the most important compounds of aromatic oil components, and their percentage ranged between 0.16 and 1.12%, represented by terpene compounds and oxygenic compounds (alcohols and esters).…”
Section: Resultsmentioning
confidence: 99%
“…Biomass is pyrolyzed under anaerobic (oxygen-controlled) conditions to produce biochar. Pyrolysis involves heating a variety of organic wastes to temperatures ranging from 200 to 900°C (Širić et al, 2022 ). The application of Biochar results in plant development and the reduction of plant diseases (Elad et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%